The D-linking effect on extraction from islands and non-islands - Goodall, Grant (Frontiers in Psychology, 2015)
“D-linked” wh-phrases such as 'which car' are known to increase the acceptability of sentences with island violations. One influential account of this attributes the effect to working memory: the D-linked filler is easier to retrieve at the site of the gap and this leads to the amelioration in acceptability. Such an account predicts that this effect should occur in general with non-trivial wh-dependencies, not just in island environments. An experiment is presented here to test this prediction. Wh-questions with both D-linked and bare wh-phrases and with both island and non-island embedded clauses are presented to participants, who rate their acceptability on a 7-point scale. Results show that D-linking significantly increases acceptability in both island and non-island environments, in accord with analyses that attribute the effect to working memory. In addition, the increase in acceptability is uniform in both types of environments, suggesting that the island effect itself may not be attributable to working memory.